Effective interventions for the induction of labor: A systematic review - Vida Ghasemi; Farzaneh Rashidi Fakari; Abbas Ebadi; Giti Ozgoli; Nourossadat Kariman; Marzieh Saei Gharenaz (Mashhad University of Medical Sciences, 2018)
Introduction: The spontaneous onset of labor and delivery are influenced by several factors. However, labor sometimes does not start on the due date. This would result in increased maternal and fetal complications and costs. Many studies have investigated the effective treatments for labor induction. The present study was performed to systematically review the studies examining the effective interventions to induce labor in Iran. material: This systematic review was conducted on the clinical trials published in the Persian and English languages. The searching process was performed in several databases, including Google scholar, Scopus, IranMedex, SID, Medlib, Magiran, IRCT, and PubMed, using the following English keywords and their Persian equivalents: "Labor", "Labor induction", "Delivery", "Initiation of labor", "Clinical trial", and "Labor pain". The articles, which obtained the score of ≥ 3 based on Jadad criteria, were entered to the study. The data were analyzed through qualitative methods.  Results: The searching process resulted in the inclusion of 29 clinical trials, 23 and 6 cases of which investigated pharmacological treatments (including 17 chemical drugs and 6 herbal drugs) and non-pharmacological treatments, respectively. According to the results of the reviewed articles, misoprostol was found to be a more effective treatment for the induction of labor than other methods. In addition, among the herbal remedies, Peganum harmala, Descurainia sophia, chamomile, and castor oil and among the non-pharmacological methods, Laminaria were reported to have a positive effect on labor induction. Conclusion: There are many types of pharmacological and nonpharmacological treatments for the induction of labor. Misoprostol was reported to be more effective in labor induction in the majority of the retrieved articles, revealing positive results in this regard. Furthermore, the use of Peganum harmala, Descurainia sophia, chamomile, castor oil, and Laminaria were proposed as effective methods for the induction of labor. However, the confirmation of the efficacy of these methods requires the implementation of further studies with a stronger methodology.